Endothelin-1 promotes human germinal vesicle-stage oocyte maturation by downregulating connexin-26 expression in cumulus cells. (8th November 2017) - Cui, Long; Shen, Jiajie; Fang, Li; Mao, Xiaodan; Wang, Hanzhi; Ye, Yinghui
Abstract: STUDY QUESTION: Does endothelin-1 (ET-1) promote human oocyte maturation and by what mechanism? SUMMARY ANSWER: Addition of ET-1 to the medium in which human germinal vesicle (GV)-stage immature oocytes are cultured enhances the GV breakdown (GVBD) rate; the resumption of meiosis may be initiated by ET-1 downregulating the expression of connexin-26 (Cx26) in cumulus cells via endothelin receptor type B (ETRB), leading to decreased cAMP levels in the oocyte. WHAT IS KNOWN ALREADY: The paracrine factor ET-1 is secreted by ovarian somatic cells in pre-ovulatory follicles and regulates oocyte maturation in mice. Connexins, or gap junction proteins, form intercellular membrane channels that play important roles in the resumption of meiosis. STUDY DESIGN, SIZE, DURATION: This laboratory study was conducted over a 1-year period. The effects of ET-1 on meiotic resumption were evaluated in human GV-stage cumulus-oocyte complexes (COCs; 70 oocytes/group). The transcriptome profiles of ET-1-treated or untreated cumulus cells were compared to explore the possible mechanisms by which ET-1 may regulate oocyte maturation. PARTICIPANTS/MATERIALS, SETTING, METHODS: The ET-1, ETRA and ETRB expression levels in human cumulus cells from oocytes at different stages of maturation were evaluated using real-time quantitative PCR. Human GV-stage COCs collected from patients undergoing IVF at a university-affiliated infertility centre were cultured with or without ET-1, and cumulus cells were subsequently denuded using hyaluronidase and cultured in α-MEM. A GeneChip® Human Transcriptome Array was applied to explore differences in the whole-genome transcriptome profiles of cumulus cells treated with or without ET-1. Real-time quantitative PCR and Western blotting were used respectively to examine Cx26 mRNA and protein levels in cumulus cells. Changes in cAMP levels in both oocytes and cumulus cells after ET-1 treatment were measured using an enzyme-linked immunosorbent assay. MAIN RESULTS AND THE ROLE OF CHANCE: Cumulus cells from MII-stage oocytes exhibited upregulated ET-1 expression, compared to those from GV-stage oocytes. The addition of ET-1 to the culture medium enhanced the GVBD rate of cumulus cell-enclosed human oocytes. Whole-genome transcriptome microarray analyses revealed significantly downregulated Cx26 expression in cumulus cells after ET-1 treatment, and this action was blocked by an ETRB antagonist. The involvement of Cx26 was further supported by the finding that ET-1 treatment led to decreased cAMP levels in oocytes but increased cAMP levels in cumulus cells. LARGE SCALE DATA: Microarray data are published in the GEO database (GSE97684). LIMITATIONS, REASONS FOR CAUTION: The heterogeneity of human COCs collected from patients undergoing IVF might affect the maturation results in vitro . Although we focused on the effects of ET-1 on human oocyte maturation in the present study, mammalian oocyte maturation is a complicated process involving many endocrine and paracrine factors. WIDER IMPLICATIONS OF THE FINDINGS: Our present study suggests that in vitro, human GV-stage oocyte maturation could be enhanced by adding ET-1 to the culture medium. In the present study, we explored the molecular mechanisms by which ET-1 initiates the resumption of meiosis and demonstrated that ET-1 promotes oocyte maturation by downregulating the expression of the gap junction protein Cx26 in cumulus cells. These results expand our understanding of the molecular mechanisms underlying mammalian oocyte maturation and provide a basis for better in-vitro maturation strategies. STUDY FUNDING AND COMPETING INTERESTS: This work was supported by grants from the China Natural Science Foundation (Grant Nos. 81170567 and 81370761). The authors declare that they have no conflicts of interest associated with this manuscript.